Age-specific association between thyroid autoimmunity and hypothyroidism in Chinese adults aged over 65 years: a cross-sectional study - Zhang, Mengjie; Ni, Wenjing; Zhang, Lina; Fan, Kuanlu; Sun, Yu; Liu, Chao; Xu, Shuhang (Frontiers in Endocrinology, 2023)
The correlation between thyroid autoimmune (TAI) and hypothyroidism in the elderly of different ages remains unclear. This study aimed to investigate the epidemiological characteristics of hypothyroidism, including subclinical hypothyroidism (Shypo) and overt hypothyroidism (Ohypo) in those aged ≥65 years from iodine adequate areas, and reveal the correlation between TAI and hypothyroidism in the elderly of different ages.: It was a cross-sectional study involving 2,443 subjects aged ≥65 years from two iodine adequate areas in China by cluster sampling. They were assigned into 65-69 years group, 70-79 years group and ≥80 years group. All subjects were surveyed by questionnaires, and received physical examinations, laboratory testing and thyroid ultrasound. Epidemiological characteristics of thyroid diseases in the elderly were compared among the three groups. Risk factors for hypothyroidism were predicted by binary logistic regression analysis.The median urinary iodine level was 238.70 (197.00, 273.70) μg/L. Thyroid peroxidase antibody or thyroglobulin antibody positivity (11.87%) and Shypo (9.13%) were common in the elderly. The prevalence of hypothyroidism in the elderly increased with age. TAI was a risk factor for Shypo (OR, 1.94; 95%CI, 1.35, 2.80; P<0.01) and Ohypo (OR, 7.64; 95%CI, 3.40, 17.19; P<0.01) in elderly Chinese. There was an agespecific correlation between TAI and hypothyroidism in the elderly. However, a significant correlation was not identified between TAI and hypothyroidism in ≥80 years group (P>0.05).